Study on electronic and optical properties of the twisted and strained MoS2/PtS2 heterogeneous interface - Deng, Shuo; Zhang, Yan; Li, Lijie (Applied surface science, 2019)
[Display omitted] •2D MoS2/PtS2 heterogeneous interface has been simulated using DFT.•Twisting and strain effects are considered in the simulation.•Optical absorption spectrum has been found to be widened by twisting and strain.•Optical absorption peak has been significantly increased for certain twisting angles. We report electronic and optical properties of the MoS2/PtS2 heterogeneous interfaces subject to various twisting angles based on the first principles simulation. In order to sustain the structural stability and avoid to have a large size cell, the optimized rotation angles of the MoS2/PtS2 heterogeneous interfaces are 19.1°, 30.0° and 40.9°. It is found from the first principle simulation that the absolute passband amplitude of the refractive index, extinction coefficient, reflectivity and absorption coefficient curves under 30.0° rotation angle are 6–12 times higher than 19.1° and 40.9° rotation angles of the MoS2/PtS2 heterogeneous interfaces. Moreover, under the 30.0° twisting angle, the absorption coefficient in the absorption spectrum can reach to or above 105/cm. The absorption spectrum has a red-shift and a broadening effect with the tensile strain, from roughly 700 nm (0% externally strain) to 1050 nm (5% externally strain). The prominent optical properties of MoS2/PtS2 heterogeneous interface under 30° rotation angle still exist after taking into consideration the spin-orbit coupling (SOC) effect. These results suggest that the MoS2/PtS2 heterogeneous interfaces will have great potential applications in tunable optoelectronic devices.